Causal rate-independent damping device using a rotary inerter damper - Wang, Boxiong; Ikago, Kohju; Kezuka, Shotaro (Frontiers in Built Environment, 2024)
The resistive force of linear viscous damping (LVD), which is commonly used as a damping model for structures, decreases proportionally as the frequency is decreased. Another linear damping model known as the rate-independent linear damping (RILD) model is used as a linear mathematical model for representing the damping characteristics of structures and their materials, which have a low frequency dependency. As the resistive force of the RILD is proportional to the displacement amplitude instead of that of the velocity, it is expected to control the seismic response displacement of low-frequency structures directly and thus effectively if it can be implemented in a physical device. In this paper, we propose the application of a causal approximation model of the RILD-based on Biot's model-that extends the order of dynamic stiffness of each branch to the second order with seismically isolated structures. A few branches of commercially available tuned viscous mass dampers with second-order dynamic stiffness are arranged in parallel in the proposed device. When the demand for isolator displacement mitigation is moderate, the proposed model simulates the performance of the RILD well. The proposed system outperforms the LVD system even when the demand for isolator displacement mitigation becomes severer.